Feasibility and Reliability of Quadriceps Muscle Power and Optimal Movement Velocity Measurements in Different Populations of Subjects - Kostka, Tomasz; Kostka, Joanna (Biology (Basel, Switzerland), 2024)
This study aimed to assess the feasibility and reliability of quadriceps maximal short-term power (Pmax) and corresponding optimal movement velocity (υopt—velocity at which the power reaches a maximum value) measurements in different populations of subjects. Five groups of subjects, fifty participants in each group, took part in the study: students; patients of the cardiac rehabilitation program; patients after stroke; older adults; and subjects of different ages who performed repetitive measurements with two different bicycles. The correlations calculated for the pairs of scores ranged from 0.93 to 0.99 for Pmax and from 0.86 to 0.96 for υopt (all with p < 0.001). Intraclass Correlations Coefficients (ICCs) varied from 0.93 to 0.98 for Pmax and from 0.86 to 0.95 for υopt. The standard error of measurement (SEM) varied from 16.9 to 21.4 W for Pmax and from 2.91 to 5.54 rotations(rot)/min for υopt. The coefficients of variation (CVs or SEM%) for Pmax and υopt in the stroke group were 10.6% and 11.4%, respectively; all other CVs were clearly lower than 10%. The minimal detectable change (MDC) varied from 46.6 to 59.3 W for Pmax and from 8.07 to 15.4 rot/min for υopt. MDC% varied from 9.53% to 29.3% for Pmax and from 8.19% to 31.7% for υopt, and was the highest in the stroke group. Therefore, the precision of measurements of Pmax and υopt was confirmed by very good indices of absolute and relative reliability. The proposed methodology is precise, safe, not time-consuming and feasible in older subjects and those with diseases.